2004
DOI: 10.1080/0305569042000224224
|View full text |Cite
|
Sign up to set email alerts
|

The impact of first‐year students' living situation on the integration process and study progress

Abstract: Students in different living situations are the central issue of this study. Large groups of first-year students not only transfer to a new educational system, but also start to live independently in rooms. The questions we answer, in this paper, are whether the students' living situations affect the integration process and how it is related to study progress. A total 782 first-year full-time students responded to questionnaires. A remarkable conclusion was that a positive effect of living independently on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In the Netherlands, higher education entails two forms of tertiary education: university education (academic oriented) and higher vocational education (practice oriented). Each curriculum in higher education consists of 60 European Credit Transfer System (ECTS) per year and it has been found that 'the number of credits earned' is an appropriate measure for students' academic progress (Beekhoven et al 2004;Van Den Berg and Hofman 2005). Each individuals' ECTS were asked half a year after the initial measurements for autism traits, intelligence and EF.…”
Section: Academic Progressmentioning
confidence: 99%
“…In the Netherlands, higher education entails two forms of tertiary education: university education (academic oriented) and higher vocational education (practice oriented). Each curriculum in higher education consists of 60 European Credit Transfer System (ECTS) per year and it has been found that 'the number of credits earned' is an appropriate measure for students' academic progress (Beekhoven et al 2004;Van Den Berg and Hofman 2005). Each individuals' ECTS were asked half a year after the initial measurements for autism traits, intelligence and EF.…”
Section: Academic Progressmentioning
confidence: 99%
“…Research on student living arrangements has involved four overlapping concerns. First, the relationship between academic success, living arrangements and integration into higher education (Beekhoven et al, 2004). Second, the impact of social inequality in relation to residence, for example, the relative ease of middle-class students in settling is compared to those from workingclass backgrounds (ibid.)…”
Section: Research Into Halls Of Residencementioning
confidence: 99%
“…Firstly, the relationship between academic success, living arrangements and integration into higher education (Beekhoven, De Jong and Van Hout, 2004). Secondly, the impact of social inequality in relation to residence, for example, the relative ease of middle class students in settling in 6 compared to those from working class backgrounds (ibid) and the influence of gender, 'race', culture and sexual orientation (Evans and Broido, 1999, Kaya and Weber, 2003, Enochs and Roland, 2006.…”
Section: Research Into Halls Of Residencementioning
confidence: 99%
“…Baker ve Schultz (1992, akt.Martin ve ark., 1999, üniversitede uyum düzeyleri düşük olan öğrencilerin akademik başarılarının da düşük olduğunu, üniversitenin psikolojik yardım merkezlerine daha çok başvurduklarını ve bu öğrencilerin okulu zamanında bitirme konusunda problem yaşadıklarını belirtmektedirler. Üniversite öğrencilerinin uyum düzeyleri; başa çıkma stratejileri (Jorgensen ve Dusek, 1990), denetim odağı (Martin ve Dixon, 1994), özyeterlik algısı (Silverthorn ve Gekoski, 1995), psikososyal faktörler (Martin ve ark., 1999), akademik başarı ve etnik köken (Strage, 2000), iyi oluş ve kişisel problemler (Beekhoven, De Song ve Van Hout, 2004), kimlik ve rol karmaşası (Killeya-Jones, 2005) gibi değişkenlerle ilişkisi açısından incelenmiştir. Araştırma bulguları; yurtlarda kalan öğrencilerin, evde kalan öğrencilere göre daha fazla kişisel problem yaşadıklarını, uyum düzeyi yüksek olan öğrencilerin sağlıklı başa çıkma stratejileri kullandıklarını göstermektedir.…”
Section: Kısa Süreli Bir Oryantasyonunclassified
“…Since the orientation program did not have a significant effect on the adaptation process of the students, emphasizing psychological elements and academic skills can be taken into consideration in order to achieve a positive impact on the students' transition processes during the planning phases of the future programs. (Beekhoven, De Song ve Van Hout, 2004).…”
mentioning
confidence: 99%